(untitled) (Research, Society and Development, 2026)
The objective of the present study is to evaluate the prevalence of molar-incisor hypomineralization (MIH) in students aged 7 to 12 years old at a public school in the city of Vitória/ES, and the perception of their parents and guardians about the impacts generated on the quality of life. To this end, a cross-sectional, quantitative and descriptive study was carried out with 310 schoolchildren. The presence and severity of MIH were assessed through intraoral clinical examination, using the European Academy of Pediatric Dentistry (EAPD) criteria. The impact on quality of life was assessed through a questionnaire with questions about the perception and concern of parents and guardians regarding their children’s complaints. The data were organized and tabulated in a Microsot Excel® spreadsheet and analyzed quantitatively and descriptively using Jamovi® Software. The prevalence of MIH among schoolchildren was 17.7%. Negative impacts were found in the following domains: oral symptoms (35.8%), functional limitations (19.3%) and aesthetic changes (24.8%). It was concluded that the clinical and structural characteristics of the tooth affected by MIH can negatively impact the biopsychosocial aspects of students.